Hemostatic Factors and Inflammatory Disease - Degen, Jay L. (Thrombosis and Haemostasis, 1999)
Vascular integrity is preserved by a sophisticated system of circulating and cell-associated hemostatic factors that control local thrombin generation, platelet deposition, and the conversion of soluble fibrinogen to an insoluble fibrin matrix.1,2 However, there is considerable evidence that hemostatic factors play both a wider physiological role than simply controlling blood loss, and a wider pathological role than simply triggering inopportune thrombotic events, such as myocardial infarction and stroke. In tissue repair, a crucial physiological process, fibrin(ogen) is thought to provide a critical provisional matrix on which cells can proliferate, organize, and carry out specialized functions. A variety of cell types specifically bind to and migrate on fibrin(ogen) matrices. These include endothelial cells, macrophages, neutrophils, smooth muscle cells, fibroblasts, and keratinocytes.3-8 Direct binding to fibrin(ogen) through both integrin [e.g., αvβ3, α1β5, αMβ2 (CD11b/CD18, Mac-1)] and non-integrin receptors (e.g., intercellular adhesion molecule (ICAM-1)) appears to contribute to these cell-fibrin interactions.8-11 Fibrin(ogen) degradation products have also been reported to have an impressive array of biological activities, including mitogenic, angiogenic, chemotactic, and immunosuppressive activities.12-14 There are now substantial data indicating that fibrin(ogen) may plays an important role in the inflammatory response15,16 and that it may, in fact, direct leukocyte transendothelial cell migration.11 Similarly, through several G-protein coupled protease-activated receptors on fibroblasts, endothelial cells, leukocytes, smooth muscle cells, and other cell types, thrombin is thought to play an important role in inflammatory and fibroproliferative responses.17 Fibrinolytic factors, such as plasmin(ogen), also appear to be important modulators of inflammation.18 Finally, host fibrinogen, prothrombin, plasminogen, plasminogen activator, and other hemostatic factors appear to be crucial to the pathogenesis and virulence of many bacterial species.19-21 Unfortunately, despite a myriad of provocative observations made using in vitro systems, there is little direct in vivo evidence supporting an important role of fibrin(ogen) or other hemostatic factors in either the inflammatory response or disease progression. Direct and definitive analyses have been hampered by the lack of an experimental means to specifically manipulate the level or structure of selected hemostatic factors in vivo. Fortunately, this experimental roadblock has been effectively removed by the development of gene-targeting and gene transfer technologies in mice (see below).